The Significance of Brain Transcranial Sonography in Burning Mouth Syndrome: a Pilot Study - Iris Zavoreo; Vanja Vučićević Boras; Dijana Zadravec; Vanja Bašić Kes; Dubravka Ciliga; Dragana Gabrić (University of Zagreb. School of Dental Medicine, 2017)
Objective: Burning mouth syndrome (BMS) is a chronic disorder which is affecting mostly postmenopausal women and is characterized by burning symptoms in the oral cavity on the clinically healthy oral mucosa. The results of previous studies suggested a possible role of peripheral and/or central neurological disturbances in these patients. The aim of this study was to analyze patients with burning mouth syndrome using transcranial sonography. Methods: By use of transcranial sonography of the brain parenchyma, substantia nigra, midbrain raphe and brain nucleus were evaluated in 20 patients with BMS (64.7±12.3 years) and 20 controls with chronic pain in the lumbosacral region (61.5±15). Statistical analysis was performed by use of Student t test with significance set at p<0.05. Results: The results of this study have shown hypoechogenicity of the substantia nigra and midbrain raphe as well as hyperechogenicity of the brain nucleus in BMS patients (p<0,05) as compared to controls. Conclusions: Altered transcranial sonography findings of the brain parenchyma, midbrain raphe and brain nucleus in patients with burning mouth syndrome might reflect central disturbances within this syndrome.